Perovskite aerogel yarn and preparation method and application thereof

By preparing fluorine-modified perovskite@SiO2 luminescent particles and spraying them onto a nanofiber membrane, followed by twisting, the problem of poor stability of perovskite quantum dots under high temperature conditions was solved. This resulted in a yarn material that combines stable luminescence at high temperatures with flexibility, thus expanding its application scenarios.

CN121931649BActive Publication Date: 2026-06-12DONGHUA UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202610368491.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-25
Publication Date
2026-06-12
Estimated Expiration
2046-03-25

AI Technical Summary

Technical Problem

Existing perovskite quantum dot materials are difficult to use stably in high-temperature environments, and it is also difficult to combine flexibility with fully inorganic high-temperature resistance, which limits their application in extreme environments.

Method used

Fluorine-modified perovskite@SiO2 luminescent particles were prepared and sprayed onto a nanofiber membrane. After twisting, perovskite aerogel yarn was formed. The stability and strength of the material were ensured by using a gradient temperature calcination process and a hydrophobic binder.

Benefits of technology

The prepared perovskite aerogel yarn exhibits stable luminescence at high temperatures, demonstrating excellent high-temperature resistance and flexibility, thus expanding its application range and making it suitable for special functional fiber materials in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121931649B_ABST
    Figure CN121931649B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of perovskite quantum dot material preparation, and relates to a perovskite aerogel yarn and a preparation method and application thereof. The preparation method comprises the following steps: mixing a silicon source, a weak alkaline catalyst, a mesoporous template and deionized water to react, and then performing washing and drying treatment to obtain a nano mesoporous SiO2 material; mixing and stirring the nano mesoporous SiO2 material with a fluorine source, a cesium source, a bromine source, a lead source and deionized water to obtain a precursor dispersion liquid; the precursor dispersion liquid is dried, calcined, washed, dried and ground to obtain fluorine-modified perovskite@SiO2 light-emitting particles; the fluorine-modified perovskite@SiO2 light-emitting particles are sprayed and coated on a nanofiber membrane, and then twisted, soaked and dried to form a perovskite aerogel yarn material. The material can still maintain high brightness and stable light-emitting performance under extreme environments such as 200 DEG C high temperature or humidity and water immersion, and significantly expands the application range of light-emitting fabrics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of perovskite quantum dot material preparation technology, specifically relating to a perovskite aerogel yarn, its preparation method, and its application. Background Technology

[0002] Cesium lead halide perovskite, a popular luminescent nanocrystalline material, not only possesses the excellent photoelectric properties commonly found in quantum dots, such as broad excitation spectra, tunable emission wavelengths, narrow emission half-width at half-maximum, and high fluorescence quantum efficiency, but also exhibits extremely high defect tolerance. Furthermore, its preparation conditions are relatively relaxed, its cost is lower, and it is easy to scale up production, demonstrating key roles in many fields such as solar cells, light-emitting diodes, X-ray imaging, and advanced anti-counterfeiting technologies, and possessing significant application value and socio-economic benefits. However, cesium lead halide perovskite is highly susceptible to degradation when exposed to oxygen, water, heat, or light, leading to the loss of its unique optical properties, which limits many applications, especially in extreme environments. To overcome this bottleneck, researchers have developed a strategy of coating perovskite with mesoporous materials, significantly improving the material's stability and durability while maintaining its excellent photoelectric properties.

[0003] Currently, several methods for preparing cesium lead halide perovskite composite materials based on silica coating have been proposed. For example, patent CN119823748A describes a fibrous mesoporous silica / perovskite composite material and its preparation method, which features adjustable pore size, large loading capacity, uniform distribution, and stable bonding. Patent CN112808282A discloses a hollow mesoporous spherical core-shell structure of cesium lead bromide perovskite@silica constructed from the outside in, i.e., first synthesizing a mesoporous silica support, and then generating perovskite in situ inside it. In addition, patent CN114891504A introduces a composite material of strontium-doped perovskite quantum dots and mesoporous silica, which further improves the stability and luminescence performance of cesium lead halide perovskite through strontium doping. Patent 14058367A introduces a perovskite quantum dot and mesoporous silica composite luminescent material, which significantly improves the solid-state luminescence efficiency and stability of perovskite quantum dots and makes them less prone to fluorescence quenching. Patent CN120865884A utilizes a novel photonic sintering technology to encapsulate perovskite quantum dots, ensuring that the material does not agglomerate while encapsulating the quantum dots with mesoporous materials, thus significantly improving the luminescence efficiency of the quantum dots. Patent CN120737839A discloses a process for preparing wash-resistant tin-based perovskite quantum dots. The perovskite quantum dots are based on a structure encapsulated in mesoporous silica, which significantly improves the stability of perovskite quantum dots and the wash resistance of textiles.

[0004] Existing perovskite quantum dots are mostly in powder or bulk form, making direct application difficult. While polymer-based composites possess some molding capability, they typically cannot be used stably at high temperatures. Currently, there is a lack of perovskite quantum dot materials that combine high-temperature resistance with polymer-based molding capability. From a material properties perspective, flexibility and all-inorganic high-temperature resistance are often difficult to achieve simultaneously: all-inorganic high-temperature resistant materials are mostly ceramic systems, which, while exhibiting excellent heat resistance, are inherently brittle and cannot withstand bending; while organic flexible materials, although possessing good mechanical deformability, are prone to irreversible softening or plastic deformation at high temperatures. Therefore, these materials still face certain limitations in practical applications, and there is an urgent need to develop more efficient encapsulation technologies to expand their application range. Summary of the Invention

[0005] The purpose of this invention is to overcome the defects of the prior art and provide a perovskite aerogel yarn, its preparation method and application.

[0006] The objective of this invention can be achieved through the following technical solutions:

[0007] A method for preparing perovskite aerogel yarn includes the following steps:

[0008] (1) A silicon source, a weakly basic catalyst, a mesoporous template and deionized water are mixed and reacted. After the reaction is completed, the mixture is washed and dried to obtain nanoporous SiO2 material.

[0009] (2) The nanoporous SiO2 material obtained in step (1) is mixed and stirred with fluorine source, cesium source, bromine source, lead source and deionized water to obtain a precursor dispersion; the precursor dispersion is then subjected to drying, calcination, washing, baking and grinding in sequence to obtain fluorine-modified perovskite@SiO2 luminescent particles.

[0010] This step involves introducing a fluorine source to regulate crystal morphology and passivate crystal defects, thereby verifying the effect of fluorine source introduction on improving the high-temperature resistance of the material. Its mechanism of action is mainly reflected in the following two aspects: 1. Crystal phase regulation: Fluorine ions (F...) - Because its ionic radius is smaller than that of the bromide ion (Br) - ), can partially replace Br at halogen sites - This increases the tolerance factor of the perovskite structure, making the crystal structure more stable. 2. Passivating crystal defects: On the one hand, F... - Able to directly occupy bromine vacancies on the surface (V Br This reduces nonradiative recombination caused by vacancy defects, which are common sources of deep-level defects in perovskite materials; on the other hand, F - It has high electronegativity and a small ionic radius, and can react with Pb. 2+It forms stronger ionic bonds, effectively anchors the octahedral structure, enhances lattice stability, inhibits ion migration and phase separation, thereby improving the material's stability to light, heat and humidity.

[0011] (3) The fluorine-modified perovskite@SiO2 luminescent particles obtained in step (2) are sprayed onto a nanofiber membrane, and then twisted, soaked and dried to form a perovskite aerogel yarn.

[0012] Further, in step (1), the silicon source is selected from one or more of tetraethyl orthosilicate, methyl orthosilicate, propyl orthosilicate, and butyl orthosilicate;

[0013] The weakly alkaline catalyst is selected from one or more of sodium hydroxide, potassium hydroxide, ammonia, tetramethylammonium hydroxide, ethylamine, triethylamine, cyclohexylamine, calcium oxide, and sodium carbonate.

[0014] The mesoporous template is selected from one or more of hexadecyltrimethylammonium bromide (CTAB), tetradecyltrimethylammonium bromide, and octadecyltrimethylammonium bromide;

[0015] The molar ratio of the silicon source, the weakly basic catalyst, and the mesoporous template is 1:(1~1.5):(0.1~0.2); based on the volume of the silicon source, 40 mL of deionized water is added for every 1 mL of silicon source.

[0016] Furthermore, in step (1), ethanol can also be added as a co-solvent to form a homogeneous system between the silicon source and deionized water, ensuring that the hydrolysis reaction proceeds uniformly; based on the volume of the silicon source, 8 mL of ethanol is added for every 1 mL of silicon source.

[0017] Further, in step (1), the reaction temperature is 25~45℃ and the reaction time is 10~15h; preferably, the reaction temperature is 35℃ and the reaction time is 12h.

[0018] The washing process uses an acidic solution; the acidic solution is a mixture of an acidic reagent and ethanol; wherein the volume ratio of the acidic reagent to ethanol is 7:200 to 10:200; the acidic reagent is selected from one or more of hydrochloric acid, nitric acid, acetic acid, and sulfuric acid; the washing temperature is 70~90℃, and the washing time is 6~10h.

[0019] The purpose of this washing step is to transfer the product to an acidic environment, causing the pH value of the system to drop sharply, which in turn causes the silanol groups on the inner surface of the silica to be protonated, changing their charge from negative to positive or neutral. This, in turn, destroys the positively charged template agent (such as CTAB) that is bound to the negatively charged mesoporous silica on the inner wall during the alkaline synthesis process through strong electrostatic interaction, thereby achieving efficient removal of the template agent.

[0020] Further, in step (2), the cesium source is selected from one or more of cesium bromide, cesium acetate, cesium carbonate, and cesium octanoate;

[0021] The bromine source is selected from one or more of lead bromide, cesium bromide, hydrobromic acid, phenylethyl ammonium bromide, octyl ammonium bromide, and zinc bromide;

[0022] The lead source is selected from one or more of lead bromide, lead iodide, lead chloride, and lead acetate.

[0023] The fluorine source is selected from one or more of potassium fluoride, lithium fluoride, and ammonium fluoride;

[0024] In this invention, silicon source, cesium source, bromine source, lead source, and fluorine source all refer to the corresponding precursor compounds;

[0025] Based on the molar amounts of cesium, bromine, lead, and fluorine contained in each of the cesium source, bromine source, lead source, and fluorine source compounds, the ratio of cesium:bromine:lead:fluorine is 1:3:1:(0.001~0.002); based on the mass of the cesium source compound, 300~600mL of deionized water is added for each gram of cesium source; the amount of the nanoporous SiO2 material added is 3 times the total mass of each of the cesium source, bromine source, and lead source compounds.

[0026] Furthermore, in step (2), the stirring temperature is controlled at 70~90℃ and the stirring time is 2~3h to accelerate ion diffusion;

[0027] The calcination process involves heating to 400°C at a rate of 2-3°C / min, then heating to 600°C at a rate of 4-6°C / min, holding at that temperature for at least 30 minutes, and then allowing it to cool naturally to room temperature.

[0028] The washing process includes ultrasonic cleaning with deionized water at a frequency of 60-80 kHz for 2-10 hours. The ultrasonic waves utilize cavitation, acceleration, and direct flow in the liquid to directly and indirectly act on the perovskite quantum dots attached to the silica surface, stripping away excess perovskite quantum dot layers and achieving a clean treatment of the mesoporous silica surface. The surface is then centrifuged at 7000-9000 rpm for 5-15 minutes. The resulting precipitate is the cleaned fluorine-modified perovskite@SiO2 luminescent particles.

[0029] The drying process is performed in a vacuum oven with a vacuum level of -0.06 to -0.1 MPa, a drying temperature of 70 to 90°C (preferably 80°C), and a drying time of 8 to 16 hours (preferably 12 hours).

[0030] The grinding time is 5-15 minutes.

[0031] Further, in step (3), the nanofiber membrane is prepared by electrospinning silica sol, first vacuum drying at 70~90℃ for 0.5~1.5h, then heating to 700~900℃ at a heating rate of 4~6℃ / min and holding for calcination for 20~40min, and then naturally cooling to room temperature; the fiber diameter in the nanofiber membrane is 200~800nm;

[0032] The spraying solvent used in the spray coating is a hydrophobic binder, which is prepared by mixing deionized water, methyltrimethoxysilane and oxalic acid in a molar ratio of 14000~16000:200:1 and stirring for 20~40 minutes.

[0033] The twisting is a single-strand fiber twisting, with the twist direction being clockwise and the twist degree being 200~300 twists / meter; by rotating the fiber bundle around its own axis, the friction between the fibers is used to bind them together, thereby forming a yarn with strength, toughness and continuity.

[0034] The solvent used for soaking is deionized water, the soaking time is 5-15 minutes, and the temperature is 10-30℃.

[0035] Furthermore, the silica sol is obtained by mixing tetraethyl orthosilicate (TEOS, chemical formula Si(OC2H5)4), deionized water, and phosphoric acid, and the resulting nanofiber membrane is a SiO2 ceramic nanofiber membrane; wherein the mass ratio of TEOS, deionized water, and phosphoric acid is (90~100):(90~100):1. The reaction mechanism mainly consists of two steps: First, under the catalysis of hydrogen ions provided by phosphoric acid, TEOS undergoes a hydrolysis reaction to generate silicic acid and ethanol; subsequently, the silicic acid generated by hydrolysis is extremely unstable and rapidly undergoes a condensation reaction to form a network structure with Si-O-Si bonds, ultimately generating silicon dioxide. In this process, phosphoric acid not only acts as a catalyst, but the phosphorus element it contains may also be combined with the silicon dioxide network through chemical bonds (such as POP, PO-Si, POC, etc.) to form a composite oxide containing phosphorus. The specific reaction formula is as follows:

[0036] (1) Hydrolysis reaction of TEOS:

[0037]

[0038] (2) Condensation reaction:

[0039] .

[0040] The electrospinning process parameters are as follows: voltage 22 kV, slide table moving distance 100 mm, spinning distance 20 cm, roller speed 50 rpm, and injection speed 0.8~1 mL / h.

[0041] Furthermore, the drying processes in steps (1) to (3) are all freeze-drying. The freeze-drying conditions are: absolute pressure of the chamber from 0.1 Pa to 100 Pa, temperature controlled between -40℃ and -5℃, and vacuum drying time of 24~48h. The instantaneous ultra-low temperature directional freeze-drying reaction uses a liquid nitrogen atmosphere and an aluminum plate cold plate, allowing for instantaneous freezing. Freeze-drying ensures the dispersibility of mesoporous silica particles and prevents agglomeration due to intermolecular forces during drying. Freeze-drying ensures that the twisted fiber achieves a hollow structure during the drying process, further improving its temperature resistance.

[0042] The particle size range of the nanoporous SiO2 material is 20~150nm, and the pore size is 4~20nm.

[0043] The perovskite in the fluorine-modified perovskite@SiO2 luminescent particles is a mixed halide perovskite CsPbBr 3-x F x It possesses an ABX3 type perovskite crystal structure, which enhances high-temperature stability based on CsPbBr3. The perovskite described is a cesium lead bromide perovskite in which some bromide ions are replaced by fluoride ions. By doping and replacing some bromide ions with fluoride ions, the inorganic framework may form more stable bond lengths and bond angles in the early stages of crystal growth, passivating the formation of certain defects and thus enhancing the luminescence intensity of the cesium lead bromide perovskite.

[0044] The present invention also provides a perovskite aerogel yarn prepared by the method described in any of the preceding claims.

[0045] The present invention also provides an application of the perovskite aerogel yarn as described above, which is used to prepare special functional fiber materials, specifically applied in the following fields: protective equipment for special operations and rescue personnel, safety signs and emergency guidance devices in extreme environments, or equipment or products that require the combination of luminescent properties and ceramic fiber properties.

[0046] The mechanism of action of this invention is as follows:

[0047] A silicon source, a weakly basic catalyst, a mesoporous template, and deionized water are mixed and reacted. When the concentration of the mesoporous template exceeds its critical micelle concentration, it self-assembles in water to form spherical micelles. Hydrophobic hydrocarbon chains aggregate inwards, while the hydrophilic, positively charged heads face outwards, forming a structure-directing template. The OH groups generated by the dissociation of the weakly basic catalyst... -Under the influence of the process, the silicon source gradually hydrolyzes to generate negatively charged silicate species. These species are adsorbed onto the surface of positively charged micelles through electrostatic interactions and undergo condensation reactions at the interface to form an inorganic silica network. This network fixes the arrangement of the micelles and encapsulates them within the silica framework, completing the self-assembly process of mesoporous silica. The subsequent acid washing step lowers the pH of the system, causing the system's charge to change from negative to positive or become electrically neutral. This promotes the protonation of the silanol groups on the silica surface, weakening and disrupting the electrostatic interaction between the silanol groups and the positively charged template agent. Simultaneously, it converts the template agent into salts readily soluble in ethanol, thus achieving template agent removal.

[0048] By precisely controlling the reaction time, mesoporous silica with uniform particle size can be obtained, ensuring the complete formation of the mesoporous structure without affecting the subsequent luminescent properties of the material.

[0049] Subsequently, the prepared mesoporous silica was mixed and stirred with cesium, bromine, lead, and fluorine sources. The lead source strongly coordinates with oxygen atoms within the pores, anchoring itself to the pore walls, and further adsorbs bromide ions through coordination to form lead-bromine crystal nuclei. Cesium ions, through relatively weak electrostatic interactions, are distributed around the lead ions to maintain the system's charge balance. At 70–90°C, the ion migration rate accelerates, promoting the rapid formation and crystallization of the perovskite precursor. The pore size of the mesoporous silica restricts the growth space of the perovskite crystals, preventing excessive growth and the formation of large grains; simultaneously, the physical confinement effect of the pore walls stabilizes the crystal lattice, suppresses non-luminescent phase transitions, and significantly improves the stability of perovskite under hydrothermal conditions. To improve the vacancy defects present in pure lead-cesium bromide perovskite, this invention introduces a fluorine source to prepare mixed halide perovskite CsPbBr. 3-x F x F - Predisposing to replace Br on the CsPbBr3 surface - The doping effect of the site is mainly reflected in the following two aspects: (1) Stabilizing the lattice structure: F - Due to its extremely high electronegativity, it interacts with the surrounding Pb 2+ Forming stronger Pb-F ionic bonds than Pb-Br bonds. As high-energy Pb-F bonds replace low-energy Pb-Br bonds, the binding force of the entire lattice is enhanced, the lattice energy is increased, and the energy required to break the lattice is increased, thereby enhancing the thermal and chemical stability of the material. (2) Passivating surface defects: F - The ionic radius is much smaller than that of Br. - When it replaces Br - After the site, surrounding Pb 2+ To F - The convergence of these bonds results in a shorter Pb-F bond length than the original Pb-Br bond length, leading to a moderate contraction of the lattice constant. This localized structural modulation effectively passivates lead vacancy defects, reduces non-radiative recombination centers, and thus improves the material's luminescence quantum yield and stability.

[0050] This invention employs a gradient-programmed calcination process: In the first stage, the temperature is slowly increased at a rate of 2-3°C / min, allowing residual solvents, unreacted organic matter, and adsorbed water to gradually evaporate and decompose, preventing damage to the mesoporous structure due to a sudden increase in vapor pressure. This also alleviates internal stress caused by the difference in thermal expansion coefficients between the silica framework and perovskite nanocrystals. In the second stage, the heating rate is increased to 4-6°C / min. At this point, the mesoporous framework has initially solidified, allowing for rapid heating to the target reaction temperature without affecting structural integrity. In the third stage, calcination is performed at a high temperature of 600°C. This causes partial dissolution of nanocrystals with numerous defects, while larger, structurally stable nanocrystals further grow, reducing grain boundaries and significantly improving crystallinity and lattice integrity. During this process, the mesoporous silica matrix undergoes moderate shrinkage, strengthening the pore walls. The surface silanol groups undergo dehydroxylation condensation with the perovskite nanocrystals, forming stable Si-O-Pb covalent bonds. Simultaneously, F… - The enhanced diffusion at high temperatures allows for more uniform penetration into the crystal lattice, ultimately resulting in robust, high-temperature-resistant fluorine-modified perovskite@SiO2 luminescent particles. The post-processing stage employs ultrasonic cleaning, utilizing the cavitation, acceleration, and direct flow effects of ultrasound in the liquid to directly and indirectly act on the perovskite quantum dots adhering to the silica surface, stripping away excess perovskite quantum dot layers and achieving a clean treatment of the mesoporous silica surface.

[0051] The obtained fluorine-modified perovskite@SiO2 luminescent particles were dispersed in a spray solvent and then atomized and uniformly loaded onto the surface of a nanofiber membrane. The spray solvent was a hydrophobic binder prepared from a mixture of deionized water, methyltrimethoxysilane, and oxalic acid; the hydrophobic binder could form Si-O-Si covalent bonds between the nanoparticles and fibers, ensuring a strong bond. Subsequently, a twisting process was used to entangle the fibers, increasing the friction and cohesion between them, significantly improving the mechanical strength and toughness of the fiber assembly. The material was then impregnated, rapidly frozen in liquid nitrogen, and freeze-dried to form a stable three-dimensional porous structure within the fiber network. This structure ensures the uniform dispersion and fixation of nanoparticles within the fibers and, through the numerous internal hollow channels, constructs a multi-layered thermal barrier, effectively blocking heat radiation transfer. Meanwhile, thanks to the freeze-drying mechanism, the ice that fixes the porous structure of the yarn directly sublimates, resulting in a yarn with a multi-layered porous structure. Under the synergistic barrier effect of the multi-layered pores and the low thermal conductivity of the silicon-based material itself, the thermal influence of external environmental heat sources on the perovskite nanocrystals inside the composite material is greatly suppressed, thereby significantly improving the luminescence stability of the perovskite nanocrystals under high temperature conditions. Finally, a high-temperature stable, superhydrophobic, all-inorganic perovskite luminescent aerogel yarn is obtained.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] (1) This invention creatively loads fluorine-modified perovskite@SiO2 luminescent particles onto a nanofiber membrane by spraying, and twists the nanofiber membrane to form an inorganic luminescent yarn doped with perovskite, which can be further woven into fiber fabrics, effectively expanding the application scenarios and scope of use of perovskite materials.

[0054] (2) This invention further optimizes and proposes that the molar ratio of cesium, bromine, lead and fluorine in each of the cesium source, bromine source, lead source and fluorine source compounds be 1:3:1:(0.001~0.002). Within this ratio range, it can ensure the full formation of perovskite nanocrystals and the efficient passivation of defects, while avoiding the formation of impurities such as PbF2, thereby maintaining the high photoluminescence efficiency of the material.

[0055] The mechanism behind this formulation design lies in the fact that mesoporous silica has a pore size range of 4–20 nm, which falls within a nanoscale confined space. Within this confined space, the diffusion and nucleation behavior of ions in the precursor dispersion differs significantly from that in the bulk solution. After being drawn into the mesoporous channels by capillary action, the ions in the precursor dispersion tend to form a single phase with the lowest energy (i.e., the fluorine-doped perovskite phase) due to the limited spatial size, rather than separating and precipitating multiple crystalline phases. This confinement effect effectively suppresses the independent nucleation and growth of impurities such as PbF2, thereby ensuring the optical properties of the material.

[0056] (3) This invention uses a gradient heating calcination process to prepare fluorine-modified perovskite@SiO2 luminescent particles: the slow heating in the low-temperature section allows impurities and residual components to fully volatilize and decompose, while the gentle heating rate significantly reduces the risk of cracking of mesoporous materials due to thermal stress; the increased heating rate in the medium-temperature section can improve calcination efficiency while ensuring structural stability; the high-temperature section causes lead bromide cesium perovskite to form more perfectly crystallized nanocrystals, and undergoes a condensation reaction with the inner wall of mesoporous silica to form stable chemical bonds, enhancing the structural strength of perovskite@SiO2 particles; at the same time, the high temperature can promote the fluorine-modified perovskite@SiO2 luminescent particles to form ... - Uniform diffusion within mesoporous channels enables effective doping and defect passivation of lead bromide cesium perovskite.

[0057] (4) This invention uses a self-developed hydrophobic binder to uniformly load fluorine-modified perovskite@SiO2 luminescent particles onto the surface of a nanofiber membrane via spraying, followed by twisting to successfully produce a fluorescent yarn with both flexibility and high-temperature resistance. This process ensures the firm adhesion and uniform distribution of perovskite particles on the fiber surface. During the subsequent freeze-drying process, a three-dimensional porous network structure is formed inside the yarn, which can effectively block heat conduction and reduce the transfer of heat to the perovskite core, thereby achieving multiple layers of heat-resistant protection.

[0058] (5) The high-temperature stable, superhydrophobic perovskite aerogel yarn prepared by this invention uses fluorine-doped cesium lead bromide perovskite as the luminescent core, and is composed of a double-layer coating structure of mesoporous silica and nanofiber membrane. It has strong luminescence performance, and the fiber can withstand temperatures up to 200℃. It can still emit fluorescence stably in extremely humid and water-containing environments (e.g., Figure 11 As shown, the fluorescence intensity remained essentially unchanged after immersion in water for 90 days. This nanofiber membrane exhibits excellent thermal insulation properties, and the twisted fluorescent fibers possess good bending resistance, mechanical strength, and high-temperature luminescence properties. It can be woven into fabric alone or combined with various chemical fibers to prepare high-strength clothing fabrics, further expanding the application fields of perovskite materials.

[0059] (6) The high-temperature stable, superhydrophobic perovskite aerogel yarn prepared by the present invention is a multifunctional composite material assembled from mesoporous silica, perovskite nanocrystals and nanofiber membranes. It has excellent high temperature resistance, superhydrophobicity and stable luminescence performance, and its comprehensive performance is significantly better than that of traditional single perovskite materials. Attached Figure Description

[0060] Figure 1 This is a schematic diagram of the preparation process of the perovskite aerogel yarn and fabric in Example 1.

[0061] Figure 2 Here are (a) SEM images and (b) particle size distribution diagrams of the nanoporous SiO2 material in Example 1;

[0062] Figure 3 The optical images of the fluorine-modified perovskite@SiO2 luminescent particles of Example 1 under (a) sunlight irradiation and (b) ultraviolet light irradiation are shown, wherein the wavelength of the ultraviolet light is 365 nm.

[0063] Figure 4 This is a SEM image of the fluorine-modified perovskite@SiO2 luminescent particles from Example 1.

[0064] Figure 5 This is a SEM image of fluorine-modified perovskite@SiO2 luminescent particles chemically bonded to silica fibers in Example 1.

[0065] Figure 6 The images show (a) surface morphology SEM image and (b) cross-sectional SEM image of the perovskite aerogel yarn of Example 1.

[0066] Figure 7 Optical images of the perovskite aerogel yarn of Example 1 under (a) sunlight and (b) ultraviolet light, wherein the wavelength of the ultraviolet light is 365 nm.

[0067] Figure 8Optical images of the perovskite aerogel yarn fabric of Example 1 under (a) sunlight and (b) ultraviolet light, wherein the wavelength of the ultraviolet light is 365 nm.

[0068] Figure 9 The perovskite aerogel yarn fabric of Example 1 is shown as a hydrophobic sample and its contact angle.

[0069] Figure 10 The images show the perovskite aerogel yarn fabric of Example 1 under (a) sunlight and (b) ultraviolet light at 200°C, where the wavelength of the ultraviolet light is 365 nm.

[0070] Figure 11 Photoluminescence spectra of perovskite aerogel yarn fabric from Example 1 after soaking in deionized water for 90 days and the unsoaked sample.

[0071] Figure 12 The images show the photoluminescence spectra of the perovskite aerogel yarn fabric of Example 1 and the perovskite aerogel yarn fabric of Comparative Example 1. Detailed Implementation

[0072] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.

[0073] Unless otherwise specified, all raw materials used in this invention are commercially available products.

[0074] Example 1

[0075] The specific preparation steps of a perovskite aerogel yarn are as follows:

[0076] (1) Preparation of nanoporous SiO2 materials

[0077] Hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, and ammonia were mixed in a molar ratio of 1:1.3:0.12. For every 1 mL of tetraethyl orthosilicate, 40 mL of deionized water and 8 mL of ethanol were added, with ethanol serving as a co-solvent to ensure a homogeneous system between the tetraethyl orthosilicate and water, guaranteeing uniform hydrolysis. The reaction was carried out at 35°C for 12 hours under reflux with circulating cooling water at 20°C. After the reaction, the resulting product suspension was centrifuged, and the solid precipitate was collected. This solid precipitate was then subjected to a series of washing steps: water washing, centrifugation, ethanol washing, centrifugation, water washing, and centrifugation. Subsequently, based on the volume of tetraethyl orthosilicate in the raw material, 200 mL of ethanol and 7 mL of hydrochloric acid were added for every 5 mL of tetraethyl orthosilicate, and the mixture was stirred at 80°C for 8 hours under this acidic environment. After stirring, the mixture was centrifuged again, and the solid precipitate was collected. This process of washing with water, centrifugation, ethanol washing, centrifugation, water washing, and centrifugation was repeated. The washed solid precipitate was then subjected to the same acid washing process twice more.

[0078] The treated solid precipitate was freeze-dried, with the absolute pressure in the chamber maintained at 1 Pa and the temperature controlled at -10±5℃ during the drying process. This resulted in the preparation of nanoporous SiO2 materials with a particle size range of 20–150 nm and a pore size range of 4–20 nm.

[0079] (2) Preparation of fluorine-modified perovskite@SiO2 luminescent particles

[0080] Cesium bromide, lead bromide, and potassium fluoride were used as raw materials, with cesium bromide serving as the cesium source and part of the bromine source, lead bromide serving as the lead source and part of the bromine source, and potassium fluoride serving as the fluorine source. The molar ratio of cesium bromide, lead bromide, and potassium fluoride was cesium bromide:lead bromide:potassium fluoride = 1:1:0.001 (corresponding to the molar ratio of each element:cesium:bromine:lead:fluorine = 1:3:1:0.001). 300 mL of deionized water was added for every gram of cesium bromide. The amount of nanoporous SiO2 material added was three times the total mass of cesium bromide and lead bromide actually fed. The above-ratioed lead bromide, cesium bromide, potassium fluoride, and nanoporous SiO2 material were sequentially added to deionized water and stirred at 80°C for 3 hours to obtain a precursor dispersion.

[0081] The precursor dispersion was rapidly frozen in liquid nitrogen and then freeze-dried. The absolute pressure in the freeze-drying chamber was maintained at 1 Pa, and the temperature was controlled at -10 ± 5 °C. The resulting dried powder was first heated to 400 °C at a rate of 2 °C / min, then heated to 600 °C at a rate of 5 °C / min and held at that temperature for 30 minutes. Heating was then stopped, and the powder was allowed to cool naturally to room temperature. The calcined powder was washed with deionized water at an ultrasonic frequency of 80 kHz for 2 hours. After washing, the powder was centrifuged at 8000 rpm for 10 minutes, and the solid precipitate was collected. The precipitate was placed in a vacuum oven and dried at -0.1 MPa and 80 °C for 12 hours, followed by grinding for 10 minutes.

[0082] (3) Preparation of nanofiber membranes

[0083] Nanofiber membranes were prepared by electrospinning using silica sol. The spinning process parameters were: voltage 22 kV, slide movement distance 100 mm, spinning distance 20 cm, roller speed 50 rpm, and pouring rate 1 mL / h. The silica sol used was prepared by mixing tetraethyl orthosilicate, deionized water, and phosphoric acid in a mass ratio of 90:90:1. The obtained nanofiber membranes were vacuum dried at 80 °C for 1 hour, then calcined at 800 °C for 30 minutes with the temperature increased at 5 °C / min, followed by natural cooling to room temperature. The diameter of the calcined nanofiber membranes was 200–800 nm.

[0084] (4) Yarn forming

[0085] Deionized water, methyltrimethoxysilane, and oxalic acid were mixed in a molar ratio of 15000:200:1 and stirred for 30 minutes to obtain a hydrophobic binder. The luminescent particles obtained in step (2) were dispersed in the hydrophobic binder at a ratio of 50 mL binder per 0.01 g of particles to obtain a luminescent particle dispersion. This dispersion must be prepared fresh for use; if left for more than 24 hours, the particles are prone to agglomeration, affecting the uniformity of the load. Subsequently, the above dispersion was sprayed onto the surface of the nanofiber membrane obtained in step (3) using a high-speed spray. The airflow speed was controlled at 80 L / min during spraying, and 0.01 g of luminescent particles were sprayed per gram of fiber membrane. The fiber membrane loaded with particles was then twisted in a single strand in a clockwise direction at a twist rate of 300 twists / meter. The twisted yarn was immersed in deionized water at 20℃ for 10 min, and then freeze-dried. The absolute pressure of the chamber was controlled at 1 Pa, the temperature at -10±5℃, and the drying time was 24 h to obtain the final perovskite aerogel yarn.

[0086] The perovskite aerogel yarns described above are knitted using a warp knitting process to produce a fabric. The specific operation is as follows: The perovskite aerogel yarns are arranged horizontally at 0.5mm intervals to form horizontal yarns. A perovskite aerogel yarn is taken as a warp yarn and passed perpendicularly through two adjacent horizontal yarns. This process is repeated until all horizontal yarns are knitted, completing the first warp yarn. Subsequent warp yarns are passed perpendicularly through all horizontal yarns in the opposite direction to the previous warp yarn. This pattern is continued until the perovskite aerogel yarn fabric of the desired size is obtained. The overall preparation process of the perovskite aerogel yarn fabric in this embodiment is as follows: Figure 1 As shown.

[0087] The structure and performance are characterized as follows:

[0088] The intermediates and final products prepared in each step of this embodiment were tested and characterized for their microstructure, optical properties, water stability, hydrophobic properties, and thermal stability. The testing equipment used included a field emission scanning electron microscope (SEM), a contact angle meter, and a photoluminescence (PL) meter. The test results and characterization analysis are as follows:

[0089] 1. Microscopic morphological characterization:

[0090] The nanoporous SiO2 material synthesized in step (1) was characterized by field emission scanning electron microscopy, and its SEM image (scale bar 200 nm) was obtained, as shown below. Figure 2 As shown in Figure a, and combined with image simulation, a silica particle size distribution map was obtained, as shown in Figure a. Figure 2 As shown in Figure b, the test results show that the particle size distribution of this nanoporous SiO2 basically conforms to a normal distribution, with a particle size range of 20~150 nm. Moreover, the particle size is smaller than the fiber diameter, which can achieve effective adhesion to the fiber during subsequent spraying.

[0091] The fluorine-modified perovskite@SiO2 luminescent particles synthesized in step (2) were characterized by field emission scanning electron microscopy (SEM) to obtain their SEM images (scale bar 200 nm), as shown below. Figure 4 As shown, the results indicate that some particles agglomerate and form larger particle agglomerates during the calcination process, but their particle size is basically ≤ fiber diameter, and will not have a direct impact on the subsequent spraying effect.

[0092] The perovskite aerogel yarn prepared in step (4) was characterized by field emission scanning electron microscopy. The SEM image (scale bar 2.00 μm) of the fluorine-modified perovskite@SiO2 luminescent particles chemically bonded to the silica fibers is shown below. Figure 5 As shown, the surface morphology SEM images and cross-sectional SEM images of the perovskite aerogel yarn are respectively as follows: Figure 6 a (scale bar is 1.00 mm) and Figure 6 As shown in b (scale bar is 400 μm). Figure 5 The results showed that the fluorine-modified perovskite@SiO2 luminescent particles were uniformly and tightly attached to the fiber surface, which could ensure the uniformity of yarn luminescence and structural stability. Figure 6 The surface morphology of yarn A is visible. After twisting, the yarn forms a tightly bound structure under the action of a hydrophobic binder, with no tendency to unravel. Figure 6 As can be seen from the cross-sectional morphology of the medium-b yarn, a large number of hollow channels are formed inside the yarn. This structure can build a multi-layer heat insulation barrier and effectively block the transfer of heat radiation.

[0093] 2. Optical performance characterization:

[0094] The fluorine-modified perovskite@SiO2 luminescent particles synthesized in step (2) were subjected to sunlight and ultraviolet light irradiation, respectively, and optical images were taken, as shown in the figures below. Figure 3 As shown in a and b. The results show that the luminescent particles can emit strong green light, indicating that step (2) successfully prepared the target fluorine-modified perovskite@SiO2 luminescent particles.

[0095] The yarn prepared in step (4) was placed under sunlight and ultraviolet light irradiation to take optical images, as shown in the figures below. Figure 7 As shown in a and b. The results show that the yarn can emit strong green light, indicating that step (4) successfully prepared a yarn that can emit light sustainably and stably.

[0096] Fabrics made from this perovskite aerogel yarn were photographed under sunlight and ultraviolet light, respectively, as shown in the images below. Figure 8 As shown in Figures a and b, the results show that the yarn fabric emits strong green light, indicating that the present invention has successfully prepared a yarn fabric with sustainable and stable luminescence. At the same time, the morphology of the front of the fabric sample verifies that the yarn has good flexibility and the luminescent particles on its surface are firmly attached without falling off.

[0097] 3. Water stability test:

[0098] The yarn prepared in Example 1 was placed in a light-protected environment and immersed in deionized water for 90 days. Subsequently, its photoluminescence (PL) intensity was tested and compared with a control sample stored under the same light-protected and sealed conditions. The test results are as follows: Figure 11 As shown in the figure. The results indicate that the peak PL intensity of the yarn sample remained almost unchanged after soaking for 90 days, demonstrating that the yarn prepared by this invention can maintain excellent luminescence stability and good water stability even under long-term water immersion conditions.

[0099] 4. Hydrophobicity test:

[0100] The hydrophobic properties of the yarn fabric prepared according to this invention were characterized using a contact angle measuring instrument. The test results are as follows: Figure 9 As shown in the figure. The results show that the water contact angle on the surface of the fabric reaches 131.9°, which is much greater than 90°, indicating that the fabric prepared by this invention has good hydrophobic properties and belongs to the category of waterproof fabrics.

[0101] 5. Thermal stability test:

[0102] The yarn fabric prepared in this embodiment was heated on a hot table, and its luminescence properties were dynamically observed under ultraviolet light (wavelength 365nm). The test results are as follows: Figure 10 As shown in the figure. The results show that even when heated at 200℃ for 10 min (a temperature far exceeding the human body's tolerance temperature), the fabric still emits strong fluorescence and does not exhibit the melting or deformation phenomena commonly seen in ordinary fabrics. This indicates that the fabric prepared by this invention has excellent thermal stability and can adapt to high-temperature environments.

[0103] In summary, the perovskite aerogel yarns and fabrics prepared by this invention can maintain good luminescence properties and structural stability even in extreme environments, and have the potential for application in harsh conditions such as special operations and high temperature and humidity.

[0104] Example 2

[0105] The specific preparation steps of a perovskite aerogel yarn are as follows:

[0106] (1) Preparation of nanoporous SiO2 materials

[0107] Tetradecyltrimethylammonium bromide, propyl orthosilicate, potassium hydroxide, and deionized water were mixed in a molar ratio of 1:1.4:0.15. For every 1 mL of propyl orthosilicate, 40 mL of deionized water and 8 mL of ethanol were added, with ethanol serving as a co-solvent to ensure a homogeneous system between the propyl orthosilicate and water, guaranteeing uniform hydrolysis. The reaction was carried out at 35°C for 15 hours under reflux with circulating cooling water at 20°C. After the reaction, the resulting dispersion was centrifuged, and the solid precipitate was collected. This precipitate was then subjected to a series of steps: water washing, centrifugation, ethanol washing, centrifugation, water washing, and centrifugation. Subsequently, based on the volume of propyl orthosilicate in the raw material, 200 mL of ethanol and 7 mL of acetic acid were added for every 5 mL of propyl orthosilicate, and the mixture was stirred at 80°C for 8 hours under this acidic environment. After stirring, the mixture was centrifuged again, and the solid precipitate was collected. This process of water washing, centrifugation, ethanol washing, centrifugation, water washing, and centrifugation was repeated. The washed solid precipitate was then subjected to the same acid washing process twice more.

[0108] The treated solid precipitate was freeze-dried, with the absolute pressure in the chamber maintained at 1 Pa and the temperature controlled at -10±5℃ during the drying process. This resulted in the preparation of nanoporous SiO2 materials with a particle size range of 20–150 nm and a pore size range of 4–20 nm.

[0109] (2) Preparation of fluorine-modified perovskite@SiO2 luminescent particles

[0110] Cesium acetate, phenylethyl ammonium bromide, lead acetate, and potassium fluoride were used as raw materials, with cesium acetate serving as the cesium source, phenylethyl ammonium bromide as the bromine source, lead acetate as the lead source, and potassium fluoride as the fluorine source. The molar ratio of cesium acetate, phenylethyl ammonium bromide, lead acetate, and potassium fluoride was cesium acetate:phenylethyl ammonium bromide:lead acetate:potassium fluoride = 1:3:1:0.001 (corresponding to the molar ratio of each element: cesium:bromine:lead:fluorine = 1:3:1:0.001). 300 mL of deionized water was added for every gram of cesium acetate. The amount of nanoporous SiO2 material added was three times the total mass of cesium acetate, phenylethyl ammonium bromide, and lead acetate. The above-ratioed cesium acetate, phenylethyl ammonium bromide, lead acetate, potassium fluoride, and nanoporous SiO2 material were sequentially added to deionized water and stirred at 80°C for 3 hours to obtain the precursor dispersion.

[0111] The precursor dispersion was rapidly frozen in liquid nitrogen and then freeze-dried. The absolute pressure in the freeze-drying chamber was maintained at 1 Pa, and the temperature was controlled at -10 ± 5 °C. The resulting dried powder was first heated to 400 °C at a rate of 2 °C / min, then heated to 600 °C at a rate of 5 °C / min and held at that temperature for 30 minutes. Heating was then stopped, and the powder was allowed to cool naturally to room temperature. The calcined powder was washed with deionized water at an ultrasonic frequency of 80 kHz for 2 hours. After washing, the powder was centrifuged at 8000 rpm for 10 minutes, and the solid precipitate was collected. The precipitate was placed in a vacuum oven and dried at -0.1 MPa and 80 °C for 12 hours, followed by grinding for 15 minutes.

[0112] (3) Preparation of nanofiber membranes

[0113] Nanofiber membranes were prepared by electrospinning using silica sol. The spinning process parameters were: voltage 22 kV, slide movement distance 100 mm, spinning distance 20 cm, roller speed 50 rpm, and pouring rate 1 mL / h. The silica sol used was prepared by mixing tetraethyl orthosilicate, deionized water, and phosphoric acid in a mass ratio of 90:90:1. The obtained nanofiber membranes were vacuum dried at 80 °C for 1 hour, then calcined at 800 °C for 30 minutes with the temperature increased at 5 °C / min, followed by natural cooling to room temperature. The diameter of the calcined nanofiber membranes was 200–800 nm.

[0114] (4) Yarn forming

[0115] Deionized water, methyltrimethoxysilane, and oxalic acid were mixed in a molar ratio of 15000:200:1 and stirred for 30 minutes to obtain a hydrophobic binder. The luminescent particles obtained in step (2) were dispersed in the hydrophobic binder at a ratio of 50 mL binder per 0.01 g of particles to obtain a luminescent particle dispersion. This dispersion must be prepared fresh for use; if left for more than 24 hours, the particles are prone to agglomeration, affecting the uniformity of the load. Subsequently, the above dispersion was sprayed onto the surface of the nanofiber membrane obtained in step (3) using a high-speed spray. The airflow speed was controlled at 80 L / min during spraying, and 0.01 g of luminescent particles were sprayed per gram of fiber membrane. The fiber membrane loaded with particles was then twisted in a single strand in a clockwise direction at a twist of 300 twists / meter. The twisted yarn was immersed in deionized water at 20℃ for 10 min, and then freeze-dried. The absolute pressure of the chamber was controlled at 1 Pa, the temperature at -10±5℃, and the drying time was 48 h to obtain the final perovskite aerogel yarn.

[0116] Example 3

[0117] The specific preparation steps of a perovskite aerogel yarn are as follows:

[0118] (1) Preparation of nanoporous SiO2 materials

[0119] Hexadecyltrimethylammonium bromide, methyl orthosilicate, and sodium hydroxide were mixed in a molar ratio of 1:1.1:0.16. For every 1 mL of methyl orthosilicate, 40 mL of deionized water and 8 mL of ethanol were added, with ethanol serving as a co-solvent to ensure a homogeneous system between the methyl orthosilicate and water, guaranteeing uniform hydrolysis. The reaction was carried out at 35°C for 10 h under reflux conditions with circulating cooling water at 20°C. After the reaction, the resulting product suspension was centrifuged, and the solid precipitate was collected. This solid precipitate was then subjected to a series of treatments: water washing, centrifugation, ethanol washing, centrifugation, water washing, and centrifugation. Subsequently, based on the volume of methyl orthosilicate in the raw material, 200 mL of ethanol and 7 mL of hydrochloric acid were added for every 5 mL of methyl orthosilicate, and the mixture was stirred at 80°C for 12 h under this acidic environment. After stirring, the mixture was centrifuged again, and the solid precipitate was collected. This process of water washing, centrifugation, ethanol washing, centrifugation, water washing, and centrifugation was repeated. The washed solid precipitate was then subjected to the same acid washing process twice more.

[0120] The treated solid precipitate was freeze-dried, with the absolute pressure in the chamber maintained at 80 Pa and the temperature controlled at -10±5℃ during the drying process. This resulted in the preparation of nanoporous SiO2 materials with a particle size range of 20–150 nm and a pore size range of 4–20 nm.

[0121] (2) Preparation of fluorine-modified perovskite@SiO2 luminescent particles

[0122] Cesium carbonate, phenylethyl ammonium bromide, lead acetate, and potassium fluoride were used as raw materials, with cesium carbonate as the cesium source, phenylethyl ammonium bromide as the bromine source, lead acetate as the lead source, and potassium fluoride as the fluorine source. The molar ratio of cesium carbonate, phenylethyl ammonium bromide, lead acetate, and potassium fluoride was cesium carbonate:phenylethyl ammonium bromide:lead acetate:potassium fluoride = 0.5:3:1:0.001 (corresponding to the molar ratio of each element: cesium:bromine:lead:fluorine = 1:3:1:0.001). 600 mL of deionized water was added for every gram of cesium carbonate. The amount of nanoporous SiO2 material added was three times the total mass of cesium carbonate, phenylethyl ammonium bromide, and lead acetate. The above-ratioed cesium carbonate, phenylethyl ammonium bromide, lead acetate, potassium fluoride, and nanoporous SiO2 material were sequentially added to deionized water and stirred at 80°C for 3 hours to obtain the precursor dispersion.

[0123] The precursor dispersion was rapidly frozen in liquid nitrogen and then freeze-dried. The absolute pressure in the freeze-drying chamber was maintained at 1 Pa, and the temperature was controlled at -10 ± 5 °C. The resulting dried powder was first heated to 400 °C at a rate of 2 °C / min, then heated to 600 °C at a rate of 5 °C / min and held at that temperature for 30 minutes. Heating was then stopped, and the powder was allowed to cool naturally to room temperature. The calcined powder was washed with deionized water at an ultrasonic frequency of 80 kHz for 2 hours. After washing, the powder was centrifuged at 8000 rpm for 10 minutes, and the solid precipitate was collected. The precipitate was placed in a vacuum oven and dried at -0.1 MPa and 80 °C for 12 hours, followed by grinding for 5 minutes.

[0124] (3) Preparation of nanofiber membranes

[0125] Nanofiber membranes were prepared by electrospinning using silica sol. The spinning process parameters were: voltage 22 kV, slide movement distance 100 mm, spinning distance 20 cm, roller speed 50 rpm, and pouring rate 1 mL / h. The silica sol used was prepared by mixing tetraethyl orthosilicate, deionized water, and phosphoric acid in a mass ratio of 90:90:1. The obtained nanofiber membranes were vacuum dried at 80 °C for 1 hour, then calcined at 800 °C for 30 minutes with the temperature increased at 5 °C / min, followed by natural cooling to room temperature. The diameter of the calcined nanofiber membranes was 200–800 nm.

[0126] (4) Yarn forming

[0127] Deionized water, methyltrimethoxysilane, and oxalic acid were mixed in a molar ratio of 15000:200:1 and stirred for 30 minutes to obtain a hydrophobic binder. The luminescent particles obtained in step (2) were dispersed in the hydrophobic binder at a ratio of 50 mL binder per 0.01 g of particles to obtain a luminescent particle dispersion. This dispersion must be prepared fresh for use; if left for more than 24 hours, the particles are prone to agglomeration, affecting the uniformity of the load. Subsequently, the above dispersion was sprayed onto the surface of the nanofiber membrane obtained in step (3) using a high-speed spray. The airflow speed was controlled at 80 L / min during spraying, and 0.01 g of luminescent particles were sprayed per gram of fiber membrane. The fiber membrane loaded with particles was then twisted in a single strand in a clockwise direction at a twist of 300 twists / meter. The twisted yarn was immersed in deionized water at 20℃ for 10 min, and then freeze-dried. The absolute pressure of the chamber was controlled at 1 Pa, the temperature at -10±5℃, and the drying time was 30 h to obtain the final perovskite aerogel yarn.

[0128] Comparative Example 1

[0129] The specific preparation steps of a perovskite aerogel yarn are as follows:

[0130] (1) Preparation of nanoporous SiO2 materials

[0131] Hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, and ammonia were mixed in a molar ratio of 1:1.3:0.12. For every 1 mL of tetraethyl orthosilicate, 40 mL of deionized water and 8 mL of ethanol were added, with ethanol serving as a co-solvent to ensure a homogeneous system between the tetraethyl orthosilicate and water, guaranteeing uniform hydrolysis. The reaction was carried out at 35°C for 12 hours under reflux with circulating cooling water at 20°C. After the reaction, the resulting product suspension was centrifuged to collect the solid precipitate. This precipitate was then subjected to a series of steps: water washing, centrifugation, ethanol washing, centrifugation, water washing, and centrifugation. Subsequently, based on the volume of tetraethyl orthosilicate in the raw material, 200 mL of ethanol and 7 mL of hydrochloric acid were added for every 5 mL of tetraethyl orthosilicate. The mixture was stirred at 80°C for 12 hours under this acidic environment. After stirring, the mixture was centrifuged again to collect the solid precipitate, and the six-step process of water washing, centrifugation, ethanol washing, centrifugation, water washing, and centrifugation was repeated. The washed solid precipitate was then subjected to the same acid washing process twice more.

[0132] The treated solid precipitate was freeze-dried, with the absolute pressure in the chamber maintained at 1 Pa and the temperature controlled at -10±5℃ during the drying process. This resulted in the preparation of nanoporous SiO2 materials with a particle size range of 20–150 nm and a pore size range of 4–20 nm.

[0133] (2) Preparation of perovskite@SiO2 luminescent particles

[0134] Cesium bromide and lead bromide were used as raw materials, with cesium bromide serving as both a cesium source and a partial bromine source, and lead bromide serving as both a lead source and a partial bromine source. The molar ratio of cesium bromide to lead bromide was cesium bromide:lead bromide = 1:1 (corresponding to a molar ratio of cesium:bromine:lead = 1:3:1). 300 mL of deionized water was added for every gram of cesium bromide. The amount of nanoporous SiO2 material added was three times the total mass of the actual cesium bromide and lead bromide used. The lead bromide, cesium bromide, and nanoporous SiO2 material were sequentially added to deionized water and stirred at 80°C for 3 hours to obtain a precursor dispersion.

[0135] The precursor dispersion was rapidly frozen in liquid nitrogen and then freeze-dried. The absolute pressure in the freeze-drying chamber was maintained at 1 Pa, and the temperature was controlled at -10 ± 5 °C. The resulting dried powder was first heated to 400 °C at a rate of 2 °C / min, then heated to 600 °C at a rate of 5 °C / min and held at that temperature for 30 minutes. Heating was then stopped, and the powder was allowed to cool naturally to room temperature. The calcined powder was washed with deionized water at an ultrasonic frequency of 80 kHz for 2 hours. After washing, the powder was centrifuged at 8000 rpm for 10 minutes, and the solid precipitate was collected. The precipitate was placed in a vacuum oven and dried at -0.1 MPa and 80 °C for 12 hours, followed by grinding for 10 minutes.

[0136] (3) Preparation of nanofiber membranes

[0137] Nanofiber membranes were prepared by electrospinning using silica sol. The spinning process parameters were: voltage 22 kV, slide movement distance 100 mm, spinning distance 20 cm, roller speed 50 rpm, and pouring rate 1 mL / h. The silica sol used was prepared by mixing tetraethyl orthosilicate, deionized water, and phosphoric acid in a mass ratio of 90:90:1. The obtained nanofiber membranes were vacuum dried at 80 °C for 1 hour, then calcined at 800 °C for 30 minutes with the temperature increased at 5 °C / min, followed by natural cooling to room temperature. The diameter of the calcined nanofiber membranes was 200–800 nm.

[0138] (4) Yarn forming

[0139] Deionized water, methyltrimethoxysilane, and oxalic acid were mixed in a molar ratio of 15000:200:1 and stirred for 30 minutes to obtain a hydrophobic binder. The luminescent particles obtained in step (2) were dispersed in the hydrophobic binder at a ratio of 50 mL binder per 0.01 g of particles to obtain a luminescent particle dispersion. This dispersion must be prepared fresh for use; if left for more than 24 hours, the particles are prone to agglomeration, affecting the uniformity of the load. Subsequently, the above dispersion was sprayed onto the surface of the nanofiber membrane obtained in step (3) using a high-speed spray. The airflow speed was controlled at 80 L / min during spraying, and 0.01 g of luminescent particles were sprayed per gram of fiber membrane. The fiber membrane loaded with particles was then twisted in a single strand in a clockwise direction at a twist of 300 twists / meter. The twisted yarn was immersed in deionized water at 20℃ for 10 min, and then freeze-dried. The absolute pressure of the chamber was controlled at 1 Pa, the temperature at -10±5℃, and the drying time was 24 h to obtain the final perovskite aerogel yarn.

[0140] The photoluminescence (PL) intensity of the yarn obtained in Comparative Example 1 was tested, and the results were compared and analyzed with those of the yarn obtained in Example 1. The test results are as follows: Figure 12 As shown in the figure. The results show that the yarn prepared using the unfluorinated perovskite@SiO2 luminescent particles of Comparative Example 1 has a significantly lower PL relative strength than the yarn prepared using the fluorinated perovskite@SiO2 luminescent particles of Example 1 of this invention. This confirms that fluorine doping treatment can effectively improve the luminescence efficiency of perovskite@SiO2 luminescent particles, thereby enabling the prepared yarn to have better performance in complex environments.

[0141] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing perovskite aerogel yarn, characterized in that, Includes the following steps: (1) A silicon source, a weakly basic catalyst, a mesoporous template and deionized water are mixed and reacted. After the reaction is completed, the mixture is washed and dried to obtain nanoporous SiO2 material. (2) The nanoporous SiO2 material obtained in step (1) is mixed and stirred with fluorine source, cesium source, bromine source, lead source and deionized water to obtain a precursor dispersion; the precursor dispersion is then subjected to drying, calcination, washing, baking and grinding in sequence to obtain fluorine-modified perovskite@SiO2 luminescent particles. (3) The fluorine-modified perovskite@SiO2 luminescent particles obtained in step (2) are sprayed onto a nanofiber membrane, and then twisted, soaked and dried to form a perovskite aerogel yarn. In step (3), the nanofiber membrane is prepared by electrospinning silica sol, first vacuum drying at 70~90℃ for 0.5~1.5h, then heating to 700~900℃ at a heating rate of 4~6℃ / min and holding for calcination for 20~40min, and then naturally cooling to room temperature; the fiber diameter in the nanofiber membrane is 200~800nm. The spraying solvent used in the spray coating is a hydrophobic binder, which is prepared by mixing deionized water, methyltrimethoxysilane and oxalic acid in a molar ratio of 14000~16000:200:1 and stirring for 20~40 minutes. The drying process in steps (1) to (3) is freeze drying. The freeze drying conditions are: absolute pressure of the chamber is 0.1 Pa to 100 Pa, temperature is controlled between -40℃ and -5℃, and vacuum drying time is 24 to 48 hours.

2. The method for preparing perovskite aerogel yarn according to claim 1, characterized in that, In step (1), the silicon source is selected from one or more of tetraethyl orthosilicate, methyl orthosilicate, propyl orthosilicate, and butyl orthosilicate; The weakly basic catalyst is selected from one or more of ammonia, ethylamine, triethylamine, cyclohexylamine, and sodium carbonate. The mesoporous template is selected from one or more of hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, and octadecyltrimethylammonium bromide; The molar ratio of the silicon source, the weakly basic catalyst, and the mesoporous template is 1:(1~1.5):(0.1~0.2).

3. The method for preparing perovskite aerogel yarn according to claim 1, characterized in that, In step (1), the reaction temperature is 25~45℃ and the reaction time is 10~15h; The washing process uses an acidic solution; the acidic solution is a mixture of an acidic reagent and ethanol; wherein the volume ratio of the acidic reagent to ethanol is 7:200 to 10:200; the acidic reagent is selected from one or more of hydrochloric acid, nitric acid, acetic acid, and sulfuric acid.

4. The method for preparing perovskite aerogel yarn according to claim 1, characterized in that, In step (2), the cesium source is selected from one or more of cesium bromide, cesium acetate, cesium carbonate, and cesium octanoate; The bromine source is selected from one or more of lead bromide, cesium bromide, hydrobromic acid, phenylethyl ammonium bromide, octyl ammonium bromide, and zinc bromide; The lead source is selected from one or more of lead bromide, lead iodide, lead chloride, and lead acetate. The fluorine source is selected from one or more of potassium fluoride, lithium fluoride, and ammonium fluoride; Based on the molar amounts of cesium, bromine, lead, and fluorine contained in each of the cesium source, bromine source, lead source, and fluorine source compounds, the ratio of cesium element: bromine element: lead element: fluorine element is 1:3:1:(0.001~0.002); the amount of nanoporous SiO2 material added is 3 times the total mass of each of the cesium source, bromine source, and lead source compounds.

5. The method for preparing perovskite aerogel yarn according to claim 1, characterized in that, In step (2), the calcination is to raise the temperature to 400°C at a rate of 2~3°C / min, then raise the temperature to 600°C at a rate of 4~6°C / min, and hold the temperature for at least 30 minutes, and then let it cool naturally to room temperature. The washing process includes ultrasonic cleaning with deionized water at a frequency of 60-80 kHz for 2-10 hours.

6. The method for preparing perovskite aerogel yarn according to claim 1, characterized in that, In step (3), the twisting is a single-strand fiber twisting, the twist direction is clockwise, and the twist is 200~300 twists / meter; The solvent used for soaking is deionized water, the soaking time is 5-15 minutes, and the temperature is 10-30℃.

7. The method for preparing perovskite aerogel yarn according to claim 1, characterized in that, The silica sol is obtained by mixing tetraethyl orthosilicate, deionized water and phosphoric acid; The electrospinning process parameters are as follows: voltage 22 kV, slide table moving distance 100 mm, spinning distance 20 cm, roller speed 50 rpm, and injection speed 0.8~1 mL / h.

8. A perovskite aerogel yarn, characterized in that, Prepared using the method described in any one of claims 1 to 7.

9. An application of the perovskite aerogel yarn as described in claim 8, characterized in that, The perovskite aerogel yarn is used to prepare special functional fiber materials.

Citation Information

Patent Citations

  • Cesium lead bromine perovskite-coated silicon dioxide hollow mesoporous sphere core-shell structure and preparation method and application thereof

    CN112808282A

  • Fibrous mesoporous silica perovskite composite material and preparation method thereof

    CN119823748A

  • Preparation method and application of washable tin-based perovskite quantum dots

    CN120737839A

  • Method for packaging perovskite quantum dots by photon sintering

    CN120865884A

  • Preparation method of semiconductor nanocrystalline fluorescent material, semiconductor nanocrystalline fluorescent material prepared by method and application of semiconductor nanocrystalline fluorescent material

    CN110734758A